Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Talking Stick di Kelas V SD - Syahputri, Nelpi; S, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to describe the improvement of the integrated thematic learning process using the Cooperative Type Talking Stick model in grade V of primary schools. This research is a classroom action research with qualitative and quantitative approaches. This research was conducted in 2 cycles. Each cycle there are four stages, namely planning, implementing, observing, and reflecting. The subjects of the study were the teacher and 28 students. The results of the first cycle research in RPP meeting 1 obtained a percentage value of 77.8% (C) increased 88.9% at meeting 2 (B) and more increased by 94.4% in cycle II (SB). In the activities of the teacher in the first cycle the meeting obtained a percentage of 77.8% (B) increased by 88.9% in the second meeting and 91.7% (SB) increased in the second cycle. In the activities of students in the first cycle meeting 1 obtained a percentage value of 77.8% (B) increased 88.9% in the second meeting and increased 91.7% (SB) in the second cycle.  Based on these results it can be concluded that the cooperative model of the Talking Stick type can improve the integrated thematic learning process.